2018
DOI: 10.1364/josaa.35.000594
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, nonlinear phase estimation with the nonmodulated pyramid wavefront sensor

Abstract: The sensitivity of the pyramid wavefront sensor (PyWFS) has made it a popular choice for astronomical adaptive optics (AAO) systems. The PyWFS is at its most sensitive when it is used without modulation of the input beam. In nonmodulated mode, the device is highly nonlinear. Hence, all PyWFS implementations on current AAO systems employ modulation to make the device more linear. The upcoming era of 30-m class telescopes and the demand for ultra-precise wavefront control stemming from science objectives that in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Instead of using a model based approach to nonlinear wavefront reconstruction, such as done by [20,21], it is also possible to use a data-driven approach. The advantages of a data-driven approach is that it is not necessary to know the exact details of the optical system and its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using a model based approach to nonlinear wavefront reconstruction, such as done by [20,21], it is also possible to use a data-driven approach. The advantages of a data-driven approach is that it is not necessary to know the exact details of the optical system and its environment.…”
Section: Introductionmentioning
confidence: 99%
“…70,[81][82][83][84][85][86][87] Later, the development of fast model-based linear reconstructors 60,63,78,79,[88][89][90][91][92][93][94][95][96] began and experiments with nonlinear algorithms, including applications of learning approaches, were reported. 4,60,77,97,98 The algorithms reviewed in this section are split into several groups according to the common underlying model they invert or the common idea they employ for the reconstruction. Before describing the reconstruction methods, we start with one more feature that distinguishes various reconstruction approaches-the way the wavefront control is handled.…”
Section: Wavefront Reconstruction Methods Using Pyramid Sensor Datamentioning
confidence: 99%
“…For instance, it was suggested to use the four intensity patterns directly or other combinations of them. 5,6,[75][76][77] An analytical comparison of the standard difference-like data definition [Eq. 7] with the usage of the four intensities directly showed that the former one provides an improved linearity with respect to the incoming wavefront.…”
Section: Diffractive Phase Mask Approachmentioning
confidence: 99%
“…Non-linear wavefront reconstructors are considered as one possibility to handle the non-linearity effects of the pyramid sensor introduced by influences such as NCPAs. Currently, there still exist only a few attempts, e.g., [10,22,19,20,37,38,39,73] for handling the non-linearity of pyramid sensors with applications in astronomical AO. We introduce a new idea of non-linear wavefront reconstruction and propose to apply the non-linear Landweber/Landweber-Kaczmarz method.…”
Section: Introductionmentioning
confidence: 99%